2019
DOI: 10.1159/000502881
|View full text |Cite
|
Sign up to set email alerts
|

Cytology in Anal Cancer Screening: Practical Review for Clinicians

Abstract: The incidence and mortality of anal squamous cell carcinoma (SCC) are expected to continue to increase in the next 20 years. High-risk groups for anal SCC, i.e., human immunodeficiency virus (HIV)-positive patients, men who have sex with men (MSM), women with previous genital neoplasia, and solid-organ transplant recipients, have been identified. HIV-positive MSM have the highest risk, and some societies have advocated for anal cancer screening to be done in this population. Screening for anal SCC follows the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
0
18
0
1
Order By: Relevance
“…Anal cytology is routinely performed as a liquid-based cytology, using a Dacron swab and, in contrast with the procedure for the cervix, collected blindly [28]. The recommended unsatisfactory sample rate in high-risk groups (e.g., HIV-positive MSM) should be <5% [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anal cytology is routinely performed as a liquid-based cytology, using a Dacron swab and, in contrast with the procedure for the cervix, collected blindly [28]. The recommended unsatisfactory sample rate in high-risk groups (e.g., HIV-positive MSM) should be <5% [29].…”
Section: Discussionmentioning
confidence: 99%
“…The recommended unsatisfactory sample rate in high-risk groups (e.g., HIV-positive MSM) should be <5% [29]. The Bethesda terminology is normally used for classification, as it is for the cervix [28]. A proper digital anorectal examination should always be performed to detect masses suggesting anal cancer that may be missed by cytology or by HRA [17].…”
Section: Discussionmentioning
confidence: 99%
“…Among these two cancer types, HPV types 16 and 18 account for 87% of anal cancers and 84.9% of oropharyngeal cancers 57 . There is currently no standard screening for HPV‐related anal or oropharyngeal cancers, at least not in the pediatric age group, although anal cytology has been proposed and its utility is currently being evaluated for adults who are high risk for HPV‐associated malignancies, including SOT recipients 58 . The lack of screening further emphasizes the need for primary prevention strategies of HPV vaccination and behavioral counseling in reducing HPV‐related cancers.…”
Section: Secondary Preventionmentioning
confidence: 99%
“…23 Specifically, recent studies have demonstrated a true reduction in abnormal cervical cytology, cervical precancers, cervical cancers, and anal cancers with the use of HPV vaccine, [24][25][26] as well as early evidence of possible oropharyngeal cancer prevention. 27 There are currently three types of vaccines available: the quadrivalent (HPV types 6,11,16,18), licensed in 2006 for women and in 2009 for men; the bivalent (HPV types 16 & 18), licensed for women in 2009; in the United States, currently only the 9-valent (HPV types 6,11,16,18,31,33,45,52,58) is available and was approved for both women and men in 2014. 28…”
Section: Primary Pre Vention ( Vaccinati On) In the G Ener Al P Opul ...mentioning
confidence: 99%
“…Anal cancer screening is not a consensus among international societies [216]. Intraepithelial lesions are rare in the general population, which would not justify a universal screening program; however, screening for precancerous lesions in the higher-risk population should be considered, e.g., for HIV-positive, MSM, and immunocompromised patients, and women with a history of dysplasia or invasive cervical carcinoma [216][217][218][219][220].…”
Section: Hpv and Anal Cancermentioning
confidence: 99%